Austerity and Abortion in the European Union - Lima, J; Reeves, A; Billari, F; McKee, M; Stuckler, D (Oxford University Press, 2016)
Economic hardship accompanying large recessions can lead families to terminate unplanned pregnancies. To assess whether abortions have risen during the recession, we collected crude abortion data from 2000 to 2012 from Eurostat for countries that had legal abortions and complete data. Declining trends in abortion ratios between 2000 and 2009 have been reversing. Excess abortions between 2010 and 2012 totaled 10.6 abortions per 1000 pregnancies ending in abortion or birth or 6701 additional abortions (95% CI 1190-9240) with stronger effects in younger ages. Economic shocks may increase recourse to abortion. Further research should explore causal pathways and protective factors.